TERAPI TAWA UNTUK MENURUNKAN KECENDERUNGAN BURNOUT PADA GURU PENDAMPING ANAK BERKEBUTUHAN KHUSUS - Hayati, Risna; Widyana, Rahma; Sholichah, Mutingatu (Universitas Ahmad Dahlan, 2015)
AbstractThe purpose of this study was to determine the effect of laughter therapy in reducing the tendency of burnout in special needs teacher assistant. Subject of this research is 10 people with medium burnout indication, and five people of experimental group and five people of controlled group. The instrument used to measure the tendency of burnout with burnout propensity scale based on the symptoms of burnout. The experimental design uses design experimental quasi of pre-test and post-test of control group. Interventions given to subject are laugther therapy to experimental group for 8 meetings for two weeks. The quantitative analysis uses non parametric test with Mann Whitney test on gain score pre-post of experimental groups and controlled groups, its results Z value of -2,009 with significant level of 0,045 (p<0,05). The qualitative analysis is done by analyzing the result of interview and observation. The results show that there are significant differences in levels of burnout tendencies between the experimental group and the control group. The experimental group showed decrease of burnout indication while controlled group did not experience the decreasing.Keywords: burnout, laughter therapy, tendency of burnout